(untitled) (Homoeopathy for All, 2024)
India has a millennium-old, somewhat well-organized medical system called Ayurveda. Additional conventional systems that evolved a bit later (yet no less old) are Unani, Siddha, and Amichi. Additionally, homeopathy is a very common system in the nation. Even though homoeopathy arrived in India in the 18th century, it fully blended into Indian society and developed alongside other traditional systems, which is why it is regarded as a component of Indian systems of medicine. As a result, India holds the rare distinction of having seven accepted medical systems: homoeopathy, naturopathy, yoga, siddha, unani, and ayurveda. These systems are more commonly referred to as AYUSH or ISM & H (Indian systems of Medicine and Homoeopathy). Indian medical systems are unique in that they are holistic in character. These systems have endured for a very long time. ISM systems are "culturally compatible" and deeply ingrained in people’s belief systems. These systems have substantial public support.